(untitled) (GYMNASIUM, 2009)
Special knowledge is represented by the students’ knowledge form the different athletic tests required by the pre-universitary curriculum, such as sporting games (volleyball, basketball, football, handball), athletics running, jumping, throwing) and gymnastics (apparatus and floor exercises).. By comparing the acquisition level of the general and special knowledge, there is noticed a more elevated level in the case of the special knowledge, where students, besides practicing them over Physical Education classes, also find them in mass media or practice them in sports sections, etc. Gymnasium Nr. 1, Anul X, 2009 69 All these impose a new methodological attitude regarding school physical education, especially in the context of the Olympic Movement.